The Effect Of Price And Content Marketing On Skintific Product Purchase Decisions In Medan Sunggal District, North Sumatra - Eka Dewi Setia Tarigan; Ida Royani (UNIVED Press, 2024)
The aim of this research is to determine the influence of price and content marketing on purchasing decisions for Skintific products. This research uses quantitative methods. The population in this study were in Medan Sunggal Sub-district, North Sumatra. The number of samples in this research was 100 samples. Data was collected by distributing questionnaires to respondents using Google Form. The results of data processing show that the price variable has a positive and significant influence on purchasing decisions for Skintific products. The content marketing variable has a positive and significant influence on purchasing decisions for Skintific products. Simultaneous research also shows that price and content marketing also have a positive and significant influence on purchasing decisions for Skintific products